Scandals and Ethics Reform in the U.S. House of Representatives. (1st October 2016) - Basinger, Scott J.
Abstract : This article uses new data to assess the impact of the Office of Congressional Ethics, established in 2009, to investigate ethical misconduct by members of the U.S. House of Representatives. A comparison of the 6 years immediately before reform (2003–2008) and the 6 years immediately after reform (2009–2014) reveals that the number of scandals actually increased by 60% after reform. Although the number of members investigated for malfeasance increased by 220%, the number of members sanctioned remained constant. However well-intentioned the reforms, they failed to stem the tide of scandal because they did not modify members' incentives. Ironically, the reforms may have contributed to public dissatisfaction with Congress by publicizing investigations of members of Congress.